Reconstrucción de paleoambientes holocenos de la costa de Miramar (provincia de Buenos Aires, Argentina) basada en diatomeas. (Ameghiniana, 2014)
A sequence developed as a result of Holocene sea level fluctuations is described based on diatom-assemblage analysis. The 1.5 m section is close to Punta Hermengo, Miramar. Life habits and salinity tolerances of diatom taxa were used for the environmental reconstruction; multivariate analytical techniques were also applied. At the base of the section, high percentages of brackish-planktonic taxa represent a tidal channel infilling. Mesohalobous, benthical epiphytic taxa characterize the overlying sediments, suggesting a brackish, shallow, stable environment such as a swamp with a restricted connection to the sea.